ToF‐SIMS of metal‐complex‐based supramolecular architectures on oxide surfaces. (19th July 2012) - Spampinato, V.; Vitale, S.; Quici, S.; Torrisi, A.; Stepanenko, V.; Würthner, F.; Licciardello, A.
Abstract : Time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) was applied in combination with optical absorption spectroscopy for studying the anchoring of polypyridine‐based supramolecular layers on oxide surfaces, such as quartz or indium tin oxide, by means of a layer‐by‐layer method involving a self‐assembly process relying on coordination interactions that lead to the formation, at the surface, of metal‐complex‐based layers. ToF‐SIMS measurements were crucial in setting up the strategy for the preparation of the above systems, as they allowed a detailed monitoring of each preparation step and provided direct qualitative information on the successful anchoring at the surface. Optical measurements, on the other hand, provided quantitative information on the growth of the multilayers, beyond the thickness sampled by static‐SIMS. Copyright © 2012 John Wiley & Sons, Ltd.